2021
DOI: 10.1002/chem.202101056
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Visible‐Light Synthesis of Arylsulfonyl Fluorides: Scope and Mechanism

Abstract: The first metal‐free procedure for the synthesis of arylsulfonyl fluorides is reported. Under organo‐photoredox conditions, aryl diazonium salts react with a readily available SO2 source (DABSO) to afford the desired product through simple nucleophilic fluorination. The reaction tolerates the presence of both electron‐rich and ‐poor aryls and demonstrated a broad functional group tolerance. To shed the light on the reaction mechanism, several experimental techniques were combined, including fluorescence, NMR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 40 publications
(21 reference statements)
0
36
0
Order By: Relevance
“…Cyanoarenes are very attractive organophotocatalysts that have shown very interesting reactivity in photoredox catalysis. [10] This is mainly due to the electrochemical properties of their excited states,w hich range from À0.7 to À1.7 V for the reduction potentials and + 2.0 Vand greater for their oxidation potentials. [10] Recently,1 ,2,3,5-tetrakis(carbazole-9-yl)-4,6-dicyanobenzene (4CzIPN, PC10)has emerged as one of the most useful catalysts in the series,w hich besides its reduction potential, exhibits al onger excited-state lifetime because of the presence of the carbazole groups.S uch as tructure mimics those found in transition-metal photocatalysts,w here photoexcitation leads to the transfer of an electron from the HOMO of the metal atom to the LUMO of the ligands.…”
Section: Cyanoarene-based Organophotocatalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyanoarenes are very attractive organophotocatalysts that have shown very interesting reactivity in photoredox catalysis. [10] This is mainly due to the electrochemical properties of their excited states,w hich range from À0.7 to À1.7 V for the reduction potentials and + 2.0 Vand greater for their oxidation potentials. [10] Recently,1 ,2,3,5-tetrakis(carbazole-9-yl)-4,6-dicyanobenzene (4CzIPN, PC10)has emerged as one of the most useful catalysts in the series,w hich besides its reduction potential, exhibits al onger excited-state lifetime because of the presence of the carbazole groups.S uch as tructure mimics those found in transition-metal photocatalysts,w here photoexcitation leads to the transfer of an electron from the HOMO of the metal atom to the LUMO of the ligands.…”
Section: Cyanoarene-based Organophotocatalystsmentioning
confidence: 99%
“…[10] This is mainly due to the electrochemical properties of their excited states,w hich range from À0.7 to À1.7 V for the reduction potentials and + 2.0 Vand greater for their oxidation potentials. [10] Recently,1 ,2,3,5-tetrakis(carbazole-9-yl)-4,6-dicyanobenzene (4CzIPN, PC10)has emerged as one of the most useful catalysts in the series,w hich besides its reduction potential, exhibits al onger excited-state lifetime because of the presence of the carbazole groups.S uch as tructure mimics those found in transition-metal photocatalysts,w here photoexcitation leads to the transfer of an electron from the HOMO of the metal atom to the LUMO of the ligands. [42] To design new effective cyanoarene-based photocatalysts, the group of Zeitler investigated the effects of aromatic and halogen substitutions on the active core of three newly synthesized and five previously studied cyanoarenes.…”
Section: Cyanoarene-based Organophotocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Just recently, the group of Tlili reported a light mediated synthesis of arylsulfonyl fluorides from arenediazonium salts and DABSO-catalyzed by an organic photoredox-catalyst (Scheme 14). 86 Interestingly, DABSO plays a twofold role in this reaction. On the one hand it serves as the SO 2 -source to trap the formed aryl radical.…”
Section: Photoredox-catalysis Using Visible Lightmentioning
confidence: 99%
“…Interestingly, the reaction in the presence of halogen substituents gave the desired products in synthetically useful yields (15e-15h). To some extent, heterocyclic com- Very recently, we demonstrated that aryl sulfonyl fluorides could be obtained under visible-light metal-free procedures by using cyanoarenes as organophotocatalysts [35][36][37][38][39][40]. Indeed, the association of diazonium salts with DABSO in the presence or not of an external fluoride source (KHF 2 ) allows access to a wide variety of arylsulfonyl fluorides with moderate to very good yields (Scheme 12).…”
Section: Scheme 10 Fluorosulfonylation Of Aryldiazonium Saltsmentioning
confidence: 99%